PERAN IMAM MALIK DAN AL-SYAFII DALAM MEMBANGUN FIQH AL-HADIS - Moh. Yusni Amru Ghozali (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2022)
Fiqh al-hadis needs to receive more attention from modern researchers. It has yet to be widely discussed in research and separate works in the form of books, even though it is an istinbat methodology applicable to classical scholars’ scientific treasures. The need of people to understand the meaning and content of hadith is getting higher, bearing in mind that legal events that require arguments continue to grow and are complicated. the hadith becomes increasingly urgent context. Fiqh al-hadis is needed to offer an alternative that is virtuous in every time and place (salihun likulli zaman wa makan). Methodologically, the scientific work of fiqh al-hadis\ is more in-depth than the syarah} of hadith (helps the reader understand the words of hadith). Fiqh al-hadis\ is to reach wisdom, law, and position of hadith that can be seen from various sides, either sanad, Matan, even contextualizing it to the present time. Now. Through qualitative methods, this study traces the existence of Fiqh al-hadis from the books of syarah al-hadith and reliable narrations. The results of this study conclude that in the context of Fiqh al-hadis has a long and well-traced genealogy.